A preliminary observational study of flora and fauna and human activities on the coastal ecosystem of pantai Batu Hitam, Pahang, Malaysia - Chee, Kong Yap; Wan Solahudin, Wan Mohd Syazwan; Nulit, Rosimah; Noraini Binti Abu Bakar, Noraini; Baharuddin, Muhd Aqil Syukran; Aguol, Kennedy Aaron; Ismail, Mohamad Saupi; Ahmad Dwi Setyawan, .; Kumar, Krishnan; Wan, Hee Cheng; Chee, Seng Leow (Zibeline International Publishing, 2024)
This preliminary observational study investigates the biodiversity and human impact on the coastal ecosystem of Pantai Batu Hitam, located along the east coast of Pahang, Malaysia. The study on April 28, 2024 involved photographing marine and terrestrial flora and fauna along the beach to document and identify species through taxonomic classification using digital tools and field guides. A total of 24 species were identified across 14 families, showcasing the rich diversity of the ecosystem, including notable plant-animal interactions. Alongside the documentation of species, evidence of human activities such as tourism and infrastructure development were observed, with particular concern regarding plastic pollution and habitat degradation. These findings highlight the need for targeted conservation efforts and sustainable practices to protect Pantai Batu Hitam’s biodiversity while addressing the challenges posed by human activities. This study contributes to understanding the balance required between ecological preservation and local development in coastal regions.